Hypoxia‐inducible factor controls immunoregulatory properties of myeloid cells in mouse cardiac allografts – an experimental study. (13th July 2018) - Keränen, Mikko A. I.; Raissadati, Alireza; Nykänen, Antti I.; Dashkevich, Alexey; Tuuminen, Raimo; Krebs, Rainer; Johnson, Randall S.; Syrjälä, Simo O.; Lemström, Karl B.
Summary: Hypoxia‐inducible factors (HIFs) play a critical role in inflammatory properties of myeloid‐derived cells. The effect of HIFs on myeloid‐derived cell functions in organ transplantation remains unknown, however. We transplanted hearts into transgenic mice with myeloid cell‐targeted deletions of HIF‐1α or its negative regulator von Hippel–Lindau (VHL) to investigate the effects of HIF‐1α inactivation or HIF pathway activation, respectively, on ischemia‐reperfusion injury (IRI) and acute rejection. Deletion of VHL in myeloid cells enhanced mRNA expression of anti‐inflammatory genes IDO, Arg‐1, and HO‐1 in vitro . In vivo, VHL −/− myeloid‐derived cells of allograft recipients alleviated IRI and acute rejection, evidenced by reduced cardiomyocyte damage, decreased proinflammatory cytokine mRNA levels, and absence of inflammatory infiltrate at 5 days after transplantation. Ultimately, allograft survival was significantly prolonged. In vitro, VHL −/− myeloid‐derived cells dose‐dependently inhibited T‐cell proliferation. Myeloid cells with HIF‐1α‐deletion retained proinflammatory qualities in vitro and in vivo . Deletion of VHL in myeloid cells of nonimmunosuppressed cardiac allograft recipients reduced myocardial injury and acute rejection. We suggest that HIF transcription factors induce a regulatory phenotype in myeloid‐derived cells, which may be harnessed as a novel therapeutic strategy to regulate immune responses after heart transplantation.